Pemberdayaan Ibu-Ibu PKK Kelurahan Pongangan Kecamatan Gunungpati melalui Pelatihan Budidaya Jamur Tiram: Empowerment of the Family Welfare Programme Pongangan Village, Gunungpati District, Through Cultivation of Oyster Mushroom - Muji Sukur; Dwi Agus Diartono; Eddy Nurraharjo; Jati Sasongko Wibowo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The COVID-19 pandemic has been going on for two years and has disrupted the community's economy. This is because some people don't have jobs and income anymore. This condition also impacts the community in the Pongangan Gunungpati sub-district, Semarang. Some people lose their jobs due to layoffs at their companies. This condition does not make the community lose hope, especially mothers who are members of the Family Welfare Programme. They try to create jobs and businesses that can be pursued with existing capabilities and conditions. Oyster mushroom cultivation training activities in community service activities were chosen as an alternative solution; This is not because oyster mushroom cultivation does not require high capital; this can be done at home and independently. This community service is carried out through training and mentoring activities for oyster mushroom cultivation, with a material selection of locations and nurseries for the care and harvest of oyster mushrooms. The training and assistance are expected to provide knowledge and skills as essential capital in the oyster mushroom cultivation business that will be carried out.